2014
DOI: 10.1186/2193-1801-3-455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and salinity on metabolic rate of the Asiatic clam Corbicula fluminea (Müller, 1774)

Abstract: The effects of temperature and salinity on the metabolism of the Asiatic clam Corbicula fluminea (mollusca, Lamellibranchia) were studied experimentally. Firstly, three indexes of basal metabolism (oxygen consumption rate, OCR; ammonia excretion rate, AER; and CO2 emission rate, CER), patterns of diurnal rhythm and O: N ratios were measured for three size ranges (large: h = 25.54 ± 1.96 mm, medium: h = 22.07 ± 1.33 mm and small: h = 17.70 ± 1.43 mm) at two salinities (0.3‰ and 1.8‰). The results showed that: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…Xiao et al. () found that narrow salinity ranges had small effect on metabolism of C. fluminea . However, other mechanisms, such as reducing valve opening time and/or physiological responses to salinity (Dietz, Wilcox, Byrne, Lynn, & Silverman, ; McCorkle & Dietz, ; Ruiz & Souza, ), are likely to be more effective that mechanical displacement over extended periods of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao et al. () found that narrow salinity ranges had small effect on metabolism of C. fluminea . However, other mechanisms, such as reducing valve opening time and/or physiological responses to salinity (Dietz, Wilcox, Byrne, Lynn, & Silverman, ; McCorkle & Dietz, ; Ruiz & Souza, ), are likely to be more effective that mechanical displacement over extended periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Small-sized individuals contributed the most for bioturbation, presumably because smaller individuals may face less mechanical resistance (de la Huz, Lastra, & López, 2002) and are also more responsive to changes in environmental conditions (Gardner et al, 2011;Godbold, Bulling, & Solan, 2011;Werner & Gilliam, 1984). In addition, small individuals of C. fluminea have been reported to have higher metabolic requirements (Xiao et al, 2014) and, as they invest more in tissue growth than larger-sized individuals, increased particle mixing may lead to increased feeding effort. Mattice and Dye (1976) In contrast to the present study, however, Majdi, Bardon, and Gilbert (2014) tested the effects of body size on bioturbation behavior in C. fluminea with a similar approach and found that medium and large sizes contributed more to bioturbation at temperatures closer to the mid-tolerance range of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature has also been observed to influence the filtration rate and assimilation efficiency of bivalves (Widdows & Bayne ). To date, there have been many studies on the effects of temperature on the metabolic responses in marine bivalve molluscs, for example, Chlamys farreri (Yang, Zhang, Wang, He & Zhang ), Meretrix meretrix (Tang, Liu, Yang & Xiang ), Pinctada mazatlanica (Saucedo, Ocampo, Monteforte & Bervera ), Corbicula fluminea (Xiao, Li, Du, Jiang, Chen & Yu ) and Pinna nobilis (Trigos, Rafael Garcia‐March, Vicente, Tena & Torres ).…”
Section: Introductionmentioning
confidence: 99%
“…The highest abundance of Etak found was 11.9mm in length. According to the John statement, C. fluminea can also be found at the substrates with higher fine granules but maybe in small length size as found at this study area range around 11-12 mm compared to the range of shell length for small size was mentioned in guideline (19.310±1.137mm) by Xiao and Jiang (11). However, McMahon (12)stated that C. fluminea can live in a variety of substrates, but prefers sand and gravel, over silt hard surfaces.…”
Section: Fluminea Collection and Lengthmentioning
confidence: 99%